DIGITALIZATION IN THE DEVELOPMENT OF HUMAN CAPITAL AS A CONDITION FOR COMPETITIVENESS AND ECONOMIC GROWTH OF THE REPUBLIC OF KAZAKHSTAN - Baigelova A.N. (Academic Journal of Physical and Chemical Sciences, 2020)
Currently, the economy of Kazakhstan is in the process of global changes in the economic and technological structures. The situation in the labor market and educational services calls for changes in the content of education in relation to the modern requirements. Discloses a digital transformation sector: the importance of the balance of the strategy and tactics of business and society, issues involving the human capital and society in modernizing the management of the economy in terms of globalization. In the article the human capital is considered as the driving force behind the development of innovation-based economy, capable of responding to the challenges of the world civilization. Without the human capital development of a country can neither achieve sustainable economic growth, nor to create a contingent of workers who will be willing to take require retraining of workers of the future places or to compete effectively in the global economy. According to the authors the important role it is necessary to take digital technologies. It is necessary to completely review the contents of all levels of education and training in the IT-industry, in the field of organization of management through the development of digital skills. Currently, the economy of the Republic of Kazakhstan is at the stage of global changes in the economic and technological structures. The situation on the labor market and educational services necessitates changes in the content of education in relation to modern requirements. The sector of digital transformation is revealed: the importance of balancing the strategy and tactics of business and society development, the issues of involving human capital and society in managing the modernization of the economy in the context of globalization.The formation of a multicomponent information and educational environment, information and digital technologies make it possible to build completely new communications, as well as new relationships among people, the restructuring of the entire economy and society, so that our life is better and “smarter”. The modern economy is called the economy of effective human capital, which emphasizes its main role in the development and growth of the economy. Human capital is seen as the driving force behind the development of an innovative economy that can respond to the challenges of world civilization.It makes up more than half of the national wealth of each of the developing countries and the main intensive factor in economic growth and social development. The level of skills demanded by the labor market is changing rapidly, which creates both new opportunities and new risks.Without the development of human capital, countries will not be able to achieve sustainable economic growth, nor create a contingent of workers who will be ready to occupy advanced jobs for the future, or compete effectively in the global economic arena.